2023
DOI: 10.1186/s12883-023-03298-0
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for an online lifestyle modification education course for people living with multiple sclerosis: the multiple sclerosis online course (MSOC)

Abstract: Background People living with multiple sclerosis (plwMS) seek access to information on evidence-based lifestyle-related risk factors associated with multiple sclerosis (MS). As the internet has made delivery of lifestyle information increasingly accessible and cost-effective, we designed the Multiple Sclerosis Online Course (MSOC) to deliver a multimodal lifestyle modification program for plwMS. Two MS online courses were developed: the intervention course based on lifestyle recommendations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The MSOC RCT study design and course content have been comprehensively described previously [17]. We developed 2 courses in conjunction with people living with MS: the standard care course (SCC) based on the information from MS websites and the intervention course (IC) based on the Overcoming MS program.…”
Section: Msoc Rct Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The MSOC RCT study design and course content have been comprehensively described previously [17]. We developed 2 courses in conjunction with people living with MS: the standard care course (SCC) based on the information from MS websites and the intervention course (IC) based on the Overcoming MS program.…”
Section: Msoc Rct Study Designmentioning
confidence: 99%
“…We recruited participants for the MSOC RCT web-based across many Facebook (Meta Platforms, Inc) groups and MS websites and forums worldwide, as previously described [17]. The consenting participants completed a screening questionnaire on the study website to confirm eligibility: a self-reported diagnosis of MS by a physician and aged at least 18 years.…”
Section: Msoc Rct Study Designmentioning
confidence: 99%
See 1 more Smart Citation